ANALYSIS OF THR INCREASE IN CITY TRANSPORTATION FARES IN SUMATERA UTARA - Chintya Intan Utari; Anjani, Najwa; Yasir, Padlan; Gultom, Shafna Armiyah; Fadilah, Putri Maulidina; Siregar, Tiur Malasari (JURNAL KREASI RAKYAT, 2023)
This journal aims to analyze the increase in City Transportation (Angkot) fares in North Sumatra in 2023. In recent years, public transportation fares in the region have experienced significant changes. This research was conducted to understand the factors that influence the increase in public transportation fares and their impact on public transportation users in North Sumatra. The method used in this study includes primary and secondary data collection, as well as descriptive statistical analysis to analyze changes in public transportation fares.